"MUHOKAMAT UL-LUGHATAYN" AND ITS ROLE IN THE FORMATION OF TURKIC LANGUAGE THEORY (The Journal of Interdisciplinary Human Studies, 2026)
. This article examines Alisher Navoi's treatise "Muhokamat ul-Lug'atayn"("Judgment of the Two Languages"), written in the late fifteenth century, as a foundationalwork in the theoretical study of the Turkic (Chagatai) literary language. The study analyzesNavoi's comparative methodology, his critique of the linguistic hierarchy that privilegedPersian over Turkic in literary and official circles, and his systematic argumentationfor the expressive and semantic superiority of the Turkic language. The article furtherexplores the literary imagery employed in the treatise, particularly Navoi's discussionof youth and poetry, and situates the work within the broader intellectual traditionof Timurid Central Asia. Drawing on the original text and secondary scholarship, itis argued that "Muhokamat ul-Lug'atayn" represents not only a polemical defense ofTurkic but also one of the earliest examples of systematic comparative linguistics in theEastern scholarly tradition. The work continues to hold methodological relevance forcontemporary Uzbek and Turkic linguistic studies.
Keywords: Alisher Navoi; Muhokamat ul-Lug’atayn; Chagatai language; Turkic linguistics; comparative linguistics; Persian-Turkic bilingualism